Does type 1 diabetes mellitus affect Achilles tendon response to a 10 km run? A case control study. Issue 1 (December 2015) - Wong, Andrea; Docking, Sean; Cook, Jill; Gaida, James
Abstract Background Achilles tendon structure deteriorates 2-days after maximal loading in elite athletes. The load-response behaviour of tendons may be altered in type 1 diabetes mellitus (T1DM) as hyperglycaemia accelerates collagen cross-linking. This study compared Achilles tendon load-response in participants with T1DM and controls. Methods Achilles tendon structure was quantified at day-0, day-2 and day-4 after a 10 km run. Ultrasound tissue characterisation (UTC) measures tendon structural integrity by classifying pixels as echo-type I, II, III or IV. Echo-type I has the most aligned collagen fibrils and IV has the least. Results Participants were 7 individuals with T1DM and 10 controls. All regularly ran distances greater than 5 km and VISA-A scores indicated good tendon function (T1DM = 94 ± 11, control = 94 ± 10). There were no diabetic complications and HbA1c was 8.7 ± 2.6 mmol/mol for T1DM and 5.3 ± 0.4 mmol/mol for control groups. Baseline tendon structure was similar in T1DM and control groups – UTC echo-types (I-IV) and anterior-posterior thickness were allp > 0.05. No response to load was seen in either T1DM or control group over the 4-days post exercise. Conclusion Active individuals with T1DM do not have a heightened Achilles tendon response to load, which suggests no increased risk of tendon injury. We cannot extrapolate these findings to sedentary individuals with T1DM.